(untitled) (University Journal of Zoology, Rajshahi University, 2009)
Impacts of age, body weight, body conditions, and scrotal circumference on sperm abnormalities of bulls used for artificial insemination (AI) in Bangladesh have been studied. During 1997-2002, 1390 ejaculates of semen from 71 bulls from Central Cattle Breeding Station and Dairy Farm, Savar, Dhaka, Rajshahi Dairy and Cattle Improvement Farm, Rajabarihat, and District Artificial Insemination Centre, Rajshahi, were collected and examined. Total head abnormalities, free loose head, mid-piece, tail abnormalities, proximal and distal cytoplamic droplets, total tail abnormalities and total sperm abnormalities were recorded. Age of the bulls had significant effect on sperm abnormalities (P < 0.01) except for proximal cytoplasmic droplet. Similarly, body weight had significant effect (P < 0.05) except for the total head abnormalities, while body conditions had no significant effect on mid-piece, total tail abnormalities and total sperm abnormalities except for the total head abnormalities. Scrotal circumference had significant effect (P < 0.05) on all the sperm abnormalities. The present results demonstrate that the middle (8 to < 10 yrs) and older (>10 yrs) bulls having body weight of < 450 kg, very good body condition and 36 to < 38 cm scrotal circumference had the lowest sperm abnormalities. The need for semen examination for morphological abnormalities of spermatozoa in bulls to be used for AI programme is strongly implicated by this study. Key words: Bull sperm abnormalities, age, body weight, body conditions, scrotal circumference, artificial insemination (AI) doi:10.3329/ujzru.v27i0.1959 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 73-78 Â Â